Effect of the interfacial area measurement parameters on the push-out strength between fiber post and dentin - Bergoli, Cesar Dalmolin [UNESP]; Costa Lima, Julia Magalhaes da [UNESP]; Melo, Renata Marques de [UNESP]; Bottino, Marco Antonio [UNESP]; Valandro, Luiz Felipe (Elsevier B.V., 2014)
Purpose: To verify the influence of different instruments and operators on the bonding interfacial area and on the push-out bond strength values.Material and methods: Fifteen anterior human teeth (n=15) were selected, cleaned and standardized to 15 mm length. Root canals were prepared in 12 mm and the fiber posts were cemented using the RelyX U-100 cement. Three slices were obtained per tooth (N=45) and submitted to the push-out bond strength test. The bonding interfacial area (mm(2)) of each specimen was calculated based on the disc slice dimensions: coronal and apical diameter and height. The bonding area of each specimen was used to calculate the bond strength (Mpa). The dimensions were analyzed by different operators, using two instruments: G1 - Operator A with a digital caliper; G2 - Operator A with a stereomicroscope; G3 - Operator B with a digital caliper; G4 - Operator B with a digital stereomicroscope; G5 - Operator C with a digital caliper; G6 - Operator C with a stereomicroscope. The mean area was submitted to inter-operator and intra-operator analyses, while the mean area and mean of bond strength were submitted to the 2-way ANOVA with repeated measures and the Tukey test (alpha=0.05).Results: The inter-operator kappa was 0.83 to the digital caliper and 0.91 to the stereomicroscope, while the intra-operator kappa was 0.76. The operator and the measurement instrument influenced the interfacial bonding area (p=0.000 and p=0.001) and the push-out bond strength values (p=0.000 and p=0.000, respectively) of the disc slices.Conclusion: The final push-out bond strength values are influenced by the measuring instrument and by the measurer operator. (C) 2014 Published by Elsevier Ltd.
Keywords: Fiber post; Composite; Microscopy; Bond strength